2014
DOI: 10.5688/ajpe789172
|View full text |Cite
|
Sign up to set email alerts
|

The Sustained, Positive Impact of a Native American Cultures and Health Course on Students’ Education and Practice-Related Choices

Abstract: Objective. To encourage pharmacy students to elect education and practice opportunities in Native American communities, including careers with the Indian Health Service (IHS). Methods. Students in 2 elective courses were educated on various aspects of contemporary Native American life in urban and reservation environments, including cultural traditions, social and healthrelated challenges, health access disparities, and cultural approaches to health and wellness. The teachers were Native American leaders and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, students stated they wanted to have more teaching by an interaction with Native American people. Similarly, Roche and colleagues, 45 and Roche, 46 reported on courses for pharmacy students that combined intellectual learning and face-to-face interactions with Native American people. Personal reflection (journaling about their learning and experiences) was valuable for students and led them to find ways to continue interactions with the population after graduation (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, students stated they wanted to have more teaching by an interaction with Native American people. Similarly, Roche and colleagues, 45 and Roche, 46 reported on courses for pharmacy students that combined intellectual learning and face-to-face interactions with Native American people. Personal reflection (journaling about their learning and experiences) was valuable for students and led them to find ways to continue interactions with the population after graduation (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The majority (n=19) originated in Australia, 21 - 39 with the remaining from the United States (n=11), 40 - 50 Canada (n=6), 51 - 56 and New Zealand (n=4) 57 - 60 . A large proportion of disciplines focused exclusively on students in nursing (n=11), 24 , 27 , 28 , 34 , 43 , 48 - 51 , 59 , 60 with others in medicine (n=6), 21 , 25 , 32 , 35 , 38 , 58 dentistry (n=2), 31 , 57 pharmacology (n=2), 45 , 46 psychology (n=2), 22 , 37 social work (n=2), 23 , 42 audiology (n=1), 52 midwifery (n=1), 39 and the majority of an interdisciplinary makeup (n=13) 26 , 29 , 30 , 33 , 36 , 40 , 41 , 44 , 47 , 53 , 54 - 56…”
Section: Resultsmentioning
confidence: 99%
“…The direct interaction with members of the community lowers the resistance towards learning about Indigenous health, knowledge, and cultural safety (Ranzijn, McConnochie, Day, Nolan, & Wharton, 2008). Furthermore, recent studies have shown that this interaction leads to an increased interest in continuing to engage with the Indigenous community via volunteering and employment (Roche, 2014;Roche, Jones, Hinman, & Seoldo, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Reports of medical education efforts that have increased knowledge about the health professions among Native American students and that have increased health professionals' commitment to underserved populations suggest that physical proximity facilitates effective cultural learning to a greater degree than simply incorporating issues into a curriculum or learning from a distance (Austin et al 2019;Gallagher et al 2019). One immersive program where pharmacy students could live and work alongside IHS practitioners and Community Health Representatives showed a significant impact on the career choice for those students, increasing their likelihood of choosing a career that serves predominantly Native American communities (Roche, 2014). Across all measures, some respondents reported a lack of awareness about institutional resources and program-specific efforts regarding Native American communities.…”
Section: Insight From Respondent Comments Echoes Existing Reportsmentioning
confidence: 99%